Socio-Economic Study of Maize Farming Households in The Buffer Area of Mandalika Special Economic Zone Central Lombok Regency - Septiadi, Dudi; Rosmilawati, Rosmilawati; Usman, Abdullah; Hidayati, Asri (Jurnal Biologi Tropis, 2022)
The Mandalika Special Economic Zone is one of the priority areas for national economic development that aims to create new sources of economic growth in the region. Maize is a type of food crop that has great potential share in the agricultural sector, especially as fulfillment food needs in the Mandalika Special Economic Zone. The objectives of this study were 1) to analyze the income from maize cultivation in the buffer zone of the Mandalika Special Economic Zone; 2) analyze the perceptions of households producing corn in the buffer zone about the socioeconomic benefits of the existence of the Mandalika Special Economic Zone. The method used in this research is the descriptive method. The respondents in this study were farmers who planted maize in Mertak Village and it was determined that there were 30 respondents who were determined by purposive sampling. The results showed that maize farmers in the buffer zone of Mandalika Special Economic Zone earn income in one growing season with an average income from maize cultivation of IDR 15,392,760/LLG or IDR 13,502,577/ha. Also, maize farmers in the buffer zone of the Mandalika Special Economic Zone benefit from the existence of the Mandalika Special Economic Zone in the form of increasing employment, improving public facilities like; the road infrastructure is of better quality, the physical condition of educational facilities and health facilities is also improving.